ECONOMICAL AND ECOLOGICAL FRIENDLY OF GROWTH MEDIA FOR EDIBLE MUSHROOM Pleurotus ostreatus MADE OF THE COCONUT WASTE - CHRISTITA, MARGARETTA; SURYAWAN, ADY (Jurnal Biologi Udayana; Vol 22 No 1 (2018): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2018.v22.i01.p05, 2018)
The abundance of coconut waste in North Sulawesi has not been processed and used optimally, then it becomes waste for the environment. Coconut coir processing for planting medium is limited only for coconut peat (coconut husk powder). One drawback in processing coconut peat requires special equipment and the fuel is expensive. This study aimed to compare the use coconut peat and coconut coir as growing medium for white oyster mushroom. Coconut coir was cut 3cm x 2cm x 1cm in size, while the comparison medium uses a coconut peat. Compositions of both media are coconut coir / coconut peat 83%, 16% ricebran, 1% limestone, 60% water.  The result showed that coconut coir more productive than coconut peat. Coconut coir media produces 120.62 grams while the coconut peat media weighing 116.11 grams on each harvesting. Based on the result it can be conclude the usage of coconut coir was better compare than coconut peat for cultivation of oyster mushroom.   Key words: Coconut waste, coconut coir, coconut peat, media, mushroom